POTENSI ANTIPLATELET CAMPURAN EKSTRAK BINAHONG, JAHE DAN KUNYIT PADA MENCIT PUTIH JANTAN - Lusi Indriani; Moerfiah Moerfiah; Oktaviana Zunnita; Faisal Pradana (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2021)
Antiplatelets can inhibit platelets aggregation and have been used in prevention and treatment the trombotic desease. Binahong leaves, ginger dan turmeric have antiplatelets activity. The mixture of these plants are expected to increase the antiplatelets potency. This study aimed to determine the optimum dose of ethanol extracts of binahong leaves, ginger dan turmeric as antiplatelets agent. The antiplatelets testing were carried out by in vivo method using parameter of bleeding and coagulation time. The testing solutions were administered orally once a day for 8 days. There were 7 treatment groups consist of positive control (Acetosal 0.29mg/20gBW), negative control (CMC-Na 0.5%), binahong 10mg/20gBW, mixture 1 of binahong:ginger:turmeric (5:0.5:1mg/20gBW), mixture 2 (10:0.5:1mg/20gBW), mixture 3 (5:1:1mg/20gBW), and mixture 4 (5:0.5:2mg/20gBW). The bleeding and coagulation time were determined at 0, 3rd, 6th and 9th day. The bleeding time was determined by injuring mice tail, the blood that comes out were absorbed with absorption paper. From the first bleeding time until stopped was calculated as bleeding time. The coagulation time was determined by observing the formation of fibrin thread in the broken capillary pipe. The blood from the end tail were absorbed with capillary pipe, and then was broken every 15 seconds. The antiplatelets activity in mice with bleeding time parameter showed that mixture 3 was more effective at 3rd day with an increased of 16.60%, than the positive control group (3.92%). The coagulation time parameter showed that the binahong group was more effective at 9th day with an increased of 203.55%, than the positive control group (89.71%). The mixture of binahong, ginger, and turmeric were the most effective in increasing bleeding time, whereas binahong was the most effective in increasing coagulation time.